Chimera at BMC overlooking CSMT - Ghosh, Ayan (2023)
In 2018, UNESCO awarded World Heritage status to the Victorian Gothic and Art Deco ensemble of Mumbai. In its citation, UNESCO noted ’Both the Victorian Gothic and the Art Deco ensembles exhibit an important exchange of European and Indian human values over a span of time. The Victorian assemblage of grand public buildings created an Indo-Gothic style by blending Gothic Revival elements with Indian elements, with adaptations in response to the local climate by introducing balconies and verandas.’